MEDIA PEMBELAJARAN TEMATIK: MIND MAPPING SEBAGAI SOLUSI INOVATIF BAGI SEKOLAH DASAR - Nurochmah; Suidat; Muslimah; Salwa Marsela; Ignasius Tasi (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
Mind mapping, often referred to as concept mapping, is a highly effective tool for organizing thoughts and is a simple way to store information in the brain and retrieve it when needed. This research aims to: (1) identify factors contributing to inadequate design of thematic learning media in Grade III primary schools in Bogor Regency, (2) design thematic learning media based on mind mapping for implementation in Grade III primary schools in Bogor Regency, (3) evaluate teachers’ responses to the use of thematic learning media based on mind mapping in Grade III primary schools in Bogor Regency. This study adopts the ADDIE model development approach, involving Analysis, Design, Development, Implementation, and Evaluation stages. Findings indicate that thematic learning media based on mind mapping are not well-structured due to primary school teachers’ limited understanding of mind mapping creation in Bogor Regency. Expert evaluation shows the developed media received a good rating, and teachers responded positively to the developed media. This suggests that thematic learning media based on mind mapping can effectively enhance learning in primary schools in Bogor Regency.